Sportsmanship and Politics: Xenophon on Ponos and Democratic Competition. (3rd July 2018) - Avramenko, Richard; Bunting, Thomas
ABSTRACT: Even though agonistic democratic theory espouses and celebrates competition, it seemingly lacks a coherent ethic for decent winning and losing in everyday political life. This article is an effort to fill this void by suggesting a practice-based, non-perfectionist ethic drawn from sport. Focusing on Xenophon's  On Hunting, we argue that sport, properly defined, offers an appropriate experience with  ponos  (toil, suffering) that teaches citizens perseverance, humility, generosity, empathy, and stewardship. This sporting ethic, we argue, provides a more suitable model for winning and losing in public life than the martial basis of agonistic democratic theory.